1985
DOI: 10.1007/bf00393516
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA-encoded auxin formation in crown-gall cells

Abstract: The T-region of Ti plasmids expresses two genes (No. 1 and 2) in crown-gall cells which are essential for auxin effects. It has been shown that gene 2 (=IaaH) codes for an amidohydrolase which converts indole-3-acetamide into indole-3-acetic acid and which is functional in bacteria and in crown-gall cells (Schröder et al. (1984), Eur. J. Biochem. 138, 387-391). In this report we describe a quantitative assay for the enzyme and its application to analyze the properties of the enzyme as expressed in plant cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…NAM is a synthetic structural homologue of IAM and the reaction product, NAA, like IAA is a strong auxin. In agreement with this observation, a similar behavior has previously been reported for the IaaH gene product of A. tumefaciens which shows enzymatic activity not only against IAM, but also against NAM and phenylacetamide to nearly the same extend (Kemper et al 1985). The AMIl-catalyzed conversión of all other tested substrates was under 15% of the IAM valué, thus, pin-pointing AMIl to be a specific IAM hydrolase with distinct enzymatic features, differing from those of FAAH.…”
Section: Discussionsupporting
confidence: 87%
“…NAM is a synthetic structural homologue of IAM and the reaction product, NAA, like IAA is a strong auxin. In agreement with this observation, a similar behavior has previously been reported for the IaaH gene product of A. tumefaciens which shows enzymatic activity not only against IAM, but also against NAM and phenylacetamide to nearly the same extend (Kemper et al 1985). The AMIl-catalyzed conversión of all other tested substrates was under 15% of the IAM valué, thus, pin-pointing AMIl to be a specific IAM hydrolase with distinct enzymatic features, differing from those of FAAH.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, IAA-amide conjugates were the major conjugate formed in the transgenic plants. It should be noted, however, that apart from hydrolyzing indole-3-acetamide to IAA, the IaaH hydrolase has also been reported to hydrolyze other compounds in an in vitro assay (Kemper et al, 1985). In that study, the IAA-ester conjugates IAIns and IAGluc were hydrolyzed to IAA by enzyme extracts from Escherichia coli expressing iaaH, whereas IAA-amide conjugates such as IAAsp and IAGlu were not.…”
Section: Discussionmentioning
confidence: 82%
“…Those infected with Pseudomonas (Kosuge et al 1966, Morris 1986, Agrobacterium (Thomashow et al 1984, Van Onckelen et al 1985, Kemper et al 1985 or Bradyrhizobium (Sekine et al 1988), however, have been found to biosynthesize IAA via indole-3-acetamide (IAM) of the product catalyzed by tryptophan monooxygenase (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%